Long noncoding RNA Alu‐mediated p21 transcriptional regulator promotes proliferation, migration, and pipe‐formation of human microvascular endothelial cells by sponging miR‐126. Issue 12 (16th July 2019) - Song, Aiping; Feng, Rong; Gao, Jianying; Yang, Chunqing
Abstract: Peripheral artery disease (PAD) is a serious hazard to the elderly in the lower extremity atherosclerotic plaque, accompanied by a large number of angiogenesis. Long noncoding RNA Alu‐mediated p21 transcriptional regulator (APTR) exerts important functions in promoting cell growth. Therefore, we planned to research the mechanism of APTR in angiogenesis in PAD. CCK‐8 assay, flow cytometry analysis, and migration assay were to detect cell viability, apoptosis, and migration respectively. The interaction between APTR and miR‐12 was tested through luciferase activity test. In vitro angiogenesis assay was used to test the number of tubular cells. qRT‐PCR and Western blot were to test expression of APTR, miR‐126, and angiogenesis relative factors. There was spontaneously pipe‐formation in HEMC‐1 cells under matrigel condition. Knockdown of APTR inhibited cell viability and migration and reduced the number of tubular cells. Further, APTR sponged miR‐126 and downregulating miR‐126 to promote angiogenesis. Overexpression of APTR promoted cell activity and migration and increased the number of tubular cells via negatively regulating miR‐126. APTR could elevate activating phosphatidylinositol 3 kinase/protein kinase B and mitogen extracellular kinase/extracellular signal‐regulated kinase signal pathways via negatively regulating miR‐126 to promote cell proliferation, migration, and pipe‐formation. We researched the mechanism of angiogenesis that APTR elevated proliferation, migration, and pipe‐formation via negatively regulating miR‐126. Abstract : Alu‐mediated p21 transcriptional regulator (APTR) overexpression promotes proliferation, migration, and pipe‐formation; APTR sponges miR‐126 to accelerate angiogenesis; phosphatidylinositol 3 kinase/protein kinase B and mitogen extracellular kinase/extracellular signal‐regulated kinase signal pathways are activated by APTR in promoting angiogenesis.